2014
DOI: 10.4172/2151-6219.1000104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flexible Working Method on Employee Performance: An Empirical Study in Turkey

Abstract: Flexible working methods have become more popular, because they increase employees' quality of life. The number of Turkish firms that support flexible working models and help employees coordinate their work and personal life better are increasing, because employers consider their employees' personal lives as more important. Changes in sectoral scope also played an important role in creating flexible working methods. For instance, the service sector's need to support long-term projects in shipping, banking, tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 3 publications
3
11
0
1
Order By: Relevance
“…The value of eligible greater significance is equal to 1.96. Tests that researchers do indicate that there is an influence of the flexibility of working on worker satisfaction with the background of the millennial generation in a startup company in Indonesia in accordance with previous studies conducted by Altindag and Siller (2014) and Thomson (2008) which showed that there is positive and significant of workplace flexibility on worker satisfaction. In line with research conducted by McNall et al (2010) and DeCaro et al (2010) also suggests that flexible working has a positive impact on employee satisfaction.…”
Section: Hypothesis Testing Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The value of eligible greater significance is equal to 1.96. Tests that researchers do indicate that there is an influence of the flexibility of working on worker satisfaction with the background of the millennial generation in a startup company in Indonesia in accordance with previous studies conducted by Altindag and Siller (2014) and Thomson (2008) which showed that there is positive and significant of workplace flexibility on worker satisfaction. In line with research conducted by McNall et al (2010) and DeCaro et al (2010) also suggests that flexible working has a positive impact on employee satisfaction.…”
Section: Hypothesis Testing Resultssupporting
confidence: 88%
“…Influence among variables will be assessed significant and the hypothesis is accepted if the value of t is greater than t table is of members of the organization. In line with research conducted by Shagvaliyeva and Yazdanifard (2014) and ACAS (2015), Altindag and Siller (2014) also suggests that flexible working has a positive and significant impact on the loyalty of members of the organization. To see the extent to which labor flexibility and worker satisfaction affects loyalty of members of the organization with a background in the millennial generation startup companies in Indonesia, investigators conducted an analysis to see the value of factor loading of test results standardized solution.…”
Section: Hypothesis Testing Resultssupporting
confidence: 81%
“…Therefore, to overcome such responses, students' self-esteem needs to be facilitated as a "fortress" so as not to be easily trapped by various destructive responses that weakenings an individuals' commitment towards work. Individuals work faithfully because of various factors, such as the appropriateness of the job conducted (Altindag & Siller, 2014), and this loyalty is admitted and valued (Murali, Poddar, & Seema, 2017). When an individual perceives a job as fun and positive, surely that person is continually faithful to the work.…”
Section: E Self-esteem Includes Loyalty At Workmentioning
confidence: 99%
“…(r=0.283). According to Altindag and Siller (2014), flexible working arrangement not only led to employee job satisfaction but also contribute to organization's loyalty.…”
Section: Correlation Analysismentioning
confidence: 99%